A null mutation in ANGPTL8 does not associate with either plasma glucose or type 2 diabetes in humans. Issue 1 (December 2016) - Clapham, Katharine; Chu, Audrey; Wessel, Jennifer; Natarajan, Pradeep; Flannick, Jason; Rivas, Manuel; Sartori, Samantha; Mehran, Roxana; Baber, Usman; Fuster, Valentin; Scott, Robert; Rader, Daniel; et al.
Abstract Background Experiments in mice initially suggested a role for the protein angiopoietin-like 8 (ANGPTL8) in glucose homeostasis. However, subsequent experiments in model systems have challenged this proposed role. We sought to better understand the importance ofANGPTL8 in human glucose homeostasis by examining the association of a null mutation in ANGPTL8 with fasting glucose levels and risk for type 2 diabetes. Methods A naturally-occurring null mutation in humanANGPTL8 (rs145464906; c.361C > T; p.Q121X) is carried by 1 in 1000 individuals of European ancestry and is associated with higher levels of plasma high-density lipoprotein cholesterol, suggesting that this mutation has functional significance. We examined the association of p.Q121X with fasting glucose levels and risk for type 2 diabetes in up to 95, 558 individuals (14, 824 type 2 diabetics and 80, 734 controls). Results We found no significant association of p.Q121X with either fasting glucose or type 2 diabetes (p -value = 0.90 and 0.65, respectively). Given our sample sizes, we had >98 % power to detect at least a 0.23 mmol/L effect on plasma glucose and >95 % power to detect a 70 % increase in risk for type 2 diabetes. Conclusion Disruption ofANGPTL8 function in humans does not seem to have a large effect on measures of glucose tolerance.